IDEOLOGICAL SOURCES AND METHODOLOGICAL ISSUES OF THE TEACHING OF SUFISM - Mukhsimov Davron Tulkunovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the theoretical issues of the teaching of Sufism, the processes of its formation, and the aspects related to its methodological problems. Along with the study of the heritage of Sufism, which has its own place in the history of Sufism, attention is paid to the ideological sources of Sufism.